2003
DOI: 10.1097/00006982-200306000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Transpupillary Thermotherapy Threshold Parameters

Abstract: Intravenous ICG pretreatment can be used to lower the TTT threshold fluence and irradiance required to create angiographically visible lesions in the normal rabbit choriocapillaris. Damage was seen in all layers of the retina and choriocapillaris at threshold levels when TTT was used alone or in combination with ICG pretreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Pigmented rabbit is a well-established animal model for retinal laser therapy [9,12,[15][16][17], which provides conservative estimation of the damage thresholds compared to human eye. Retinal photocoagulation thresholds with 532 and 577nm wavelengths in rabbits are about 2.5 times lower than in humans [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Pigmented rabbit is a well-established animal model for retinal laser therapy [9,12,[15][16][17], which provides conservative estimation of the damage thresholds compared to human eye. Retinal photocoagulation thresholds with 532 and 577nm wavelengths in rabbits are about 2.5 times lower than in humans [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The main aim behind the use of ICG in these situations would be to make the tumor tissue containing ICG more sensitive to the thermal therapy delivered by the infrared lasers. Moreover, ICG may allow the desired clinical endpoint with reduced laser parameters [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported enhanced laser-tumor tissue photothermal interaction between the diode laser used in TTT (810 nm) and indocyanine green (ICG) dye and showed that ICG could decrease the laser fluence and irradiance threshold in TTT photocoagulation properties [5,6]. As a result, this treatment has been used in other ocular conditions such as ocular melanoma and choroidal neovascularization [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The histologic damage can be noted in the neurosensory retina even at threshold lesions, without retinal whitening (29,30). One variation of TTT involves the use of indocyanine green dye (ICG) as a thermal enhancing agent during treatment (31)(32)(33)(34)(35). Because the absorption peak of ICG dye (805 nm) is similar to the wavelength of the diode laser emission peak (810 nm), ICG dye enhances the laser photocoagulation effect, permitting use of a lower energy level than is possible without it.…”
Section: Introductionmentioning
confidence: 99%
“…The selective ablation of CNV should result in less damage to the surrounding tissues. Peyman and colleagues (34) demonstrated that by combining TTT with intravenous ICG pretreatment, the synergy resulted in a much lower TTT threshold fluence and irradiance required to create angiographically visible lesions in the normal rabbit choriocapillaris. They demonstrated a dose-dependent relationship between TTT fluence threshold and ICG concentration, with higher ICG concentration correlating to lower TTT fluence threshold.…”
Section: Introductionmentioning
confidence: 99%